Public Libraries and Access for Children with Disabilities and Their Families: A Proposed Inclusive Library Model. Issue 2 (3rd April 2017) - Kaeding, Joanne; Velasquez, Diane L.; Price, Deborah
Abstract: Within the library profession, there is widespread support for access to libraries for people with disabilities. However, there is limited literature on the topic of access to public libraries for children with disabilities and their families and very little empirical research on this topic exists. This paper reports on an investigation of factors influencing access to public libraries for children with disabilities and their families from the perspective of the public librarian. An in-depth study of 18 public librarians who focus on providing access to public libraries for children with disabilities was undertaken. Librarians from the United States and Canada took part in both a one-on-one interview and a questionnaire. Based on the research findings, a model for inclusive public libraries is proposed.